2012
DOI: 10.1186/ar3798
|View full text |Cite
|
Sign up to set email alerts
|

miR-146a, an IL-1β responsive miRNA, induces vascular endothelial growth factor and chondrocyte apoptosis by targeting Smad4

Abstract: IntroductionmiR-146a is one of the first identified miRNAs expressed differentially in osteoarthritis (OA) cartilage. However, the role it plays in OA pathogenesis is not clear. The aim of this study is to identify a molecular target of miR-146a, thereby elucidating its function in chondrocytes during OA pathogenesis.MethodsPrimary chondrocytes from Sprague-Dawley rats were treated with IL-1β before the expression levels of miR-146a, Smad4 and vascular endothelial growth factor (VEGF) were quantified by real-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
127
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 153 publications
(138 citation statements)
references
References 53 publications
9
127
0
2
Order By: Relevance
“…We were the first to identify miR‐146a as a mechanoresponsive microRNA along with miR‐365 through cytomechanical screening of microRNA microarray (Guan, Yang, Wei & Chen, 2011). Since then, multiple studies have supported the role of miR‐146a as a mechano‐miR (Huang, Crawford, Higuita‐Castro, Nana‐Sinkam & Ghadiali, 2012; Li et al., 2012). In this study, we further show that, while cyclic load of human articular chondrocytes in 3D culture in physiological range stimulated miR‐146a expression, mechanical overload inhibited miR‐146a expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We were the first to identify miR‐146a as a mechanoresponsive microRNA along with miR‐365 through cytomechanical screening of microRNA microarray (Guan, Yang, Wei & Chen, 2011). Since then, multiple studies have supported the role of miR‐146a as a mechano‐miR (Huang, Crawford, Higuita‐Castro, Nana‐Sinkam & Ghadiali, 2012; Li et al., 2012). In this study, we further show that, while cyclic load of human articular chondrocytes in 3D culture in physiological range stimulated miR‐146a expression, mechanical overload inhibited miR‐146a expression.…”
Section: Discussionmentioning
confidence: 99%
“…However, its role during OA pathogenesis is controversial with some studies suggesting a protective function while other studies indicating a destructive role in cartilage homeostasis. For example, expression of miR‐146a in chondrocytes has been proposed to contribute to OA pathogenesis by diminishing the response to TGF‐β (Li et al., 2012). A most recent study seemed to correlate with this hypothesis in vivo (Zhang et al., 2017).…”
Section: Introductionmentioning
confidence: 99%
“…This is the first report to our knowledge that identifies miR-181a-5p and miR-4454 as mediators of cartilage degeneration in FJs and potential therapeutic targets for stopping cartilage degeneration. miR-146 is another miRNA that is highly expressed in low-grade OA cartilage and is induced by IL-1β stimulation; additionally, it mediates chondrocyte apoptosis (13,14). In serum, Beyer et al recently reported miRNA let-7e as a potential predictor for severe knee or hip OA (15).…”
Section: Introductionmentioning
confidence: 99%
“…Taganov et al [26] proposed that miR-146, which is induced by IL-1 at the early-stage of OA, may control cytokine signaling pathways by down-regulating IL-1 receptorassociated kinase 1 (IRAK1) and the TNF receptorassociated factor 6 (TRAF6) levels ( Table 1). Recent analysis of IL-1 induced miR-146a in rat OA chondrocytes revealed that this miR induces VEGF expression and inhibits expression of SMAD4 (Table 1), which plays a significant role in anabolic TGF-pathway [27]. Results indicate that chondrocyte apoptosis was triggered in response to changes in expression profiles of genes regulated by miR-146a [27].…”
Section: Micrornas and Osteoarthritismentioning
confidence: 88%
“…Recent analysis of IL-1 induced miR-146a in rat OA chondrocytes revealed that this miR induces VEGF expression and inhibits expression of SMAD4 (Table 1), which plays a significant role in anabolic TGF-pathway [27]. Results indicate that chondrocyte apoptosis was triggered in response to changes in expression profiles of genes regulated by miR-146a [27].…”
Section: Micrornas and Osteoarthritismentioning
confidence: 88%